Anaerobic digestion performance of vinegar residue in continuously stirred tank reactor. (June 2015) - Li, Lin; Feng, Lu; Zhang, Ruihong; He, Yanfeng; Wang, Wen; Chen, Chang; Liu, Guangqing
Highlights: Anaerobic digestion of vinegar residue was investigated in continuous condition. CSTR showed a stable methane yield of 232.75 mL gvs −1 at OLR of 2.5 gvs  L −1  d −1 . Effluent recirculation significantly improved the stability of the AD system. Abstract: Anaerobic digestion (AD) of vinegar residue was investigated in continuously stirred tank reactor (CSTR). The influence of organic loading rate (OLR) and effluent recirculation on AD performance of vinegar residue was tested. Five OLRs, 1.0, 1.5, 2.0, 2.5, and 3.0 gvs  L −1  d −1, were used. The highest volumetric methane productivity of 581.88 mL L −1 was achieved at OLR of 2.5 gvs  L −1  d −1 . Effluent reflux ratio was set as 50%, the results showed that effluent recirculation could effectively neutralize the acidity of vinegar residue, raise the pH of the feedstock, and enhance the buffering capacity of the AD system. Anaerobic digestion of vinegar residue could be a promising way not only for converting this waste into gas energy but also alleviating environmental pollution which might be useful for future industrial application.